Pengaruh Penggunaan Media Cerita Bergambar Terhadap Keterampilan Membaca Pemahaman Siswa Sekolah Dasar - Ika Andini; Tarman Tarman; Rahmatiah Rahmatiah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to determine the effect of using picture story media on the reading comprehension skills of class III students at SD Inpres Laloasa, Parigi District, Gowa Regency. This type of research is Quasi Experimental Design research and is a quantitative type of research. The sample in this study was 19 students. Data collection techniques were carried out using learning results tests and observation sheets. The data analysis technique in this research is descriptive data analysis technique and T-Test. The research results showed that reading comprehension skills before implementing picture story media in the pretest had an average score of 45.7. Meanwhile, the posttest increased with an average score of 86.8. The results of the t-test analysis regarding the influence of picture story media on both interest and student learning outcomes show that the significance value obtained is good, namely the effect of picture story media on reading comprehension skills (Sig = 0.011) is smaller than the alpha value set at 0, 05 (0.011 < 0.05). Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted which states that there is an influence of the use of picture story media on the reading comprehension skills of class III students at SD Inpres Laloasa, Parigi District, Gowa Regency.